Reframing, refining, and reconceptualising the worst forms of child labour through participatory adaptive programming - Apgar, Marina; Burns, Danny (Journal of modern slavery, 2021)
This article explores the potential of using participatory action research as an adaptive programming modality to drive learning and innovation to tackle the drivers of (and seek to eliminate) the Worst Forms of Child Labour. We draw on our experience from early phases of implementation of a large-scale action research programme, which despite the constraints covid-19 posed in moving to full implementation and participatory engagement with children and other stakeholders on the ground, is already generating rich learning about the opportunities and challenges of designing programmes that respond to the complex reality of WFCL. We share early learning about what it takes to be fully open to using the lived experience of programme development, and early findings from scoping and mapping of the dynamics of social norms, business practices and urban neighbourhoods and supply chains influencing WFCL in Bangladesh and Nepal, to frame and reframe the questions and response strategies and operationalise a participatory adaptive intent to work with hidden and complex dynamics that characterise the WFCL.

Designing a Participatory Programme at Scale: Phases 1 and 2 of the CLARISSA Programme on Worst Forms of Child Labour - Burns, Danny; Apgar, Marina; Raw, Anna (CLARISSA Working Paper, 2021)
CLARISSA (Child Labour: Action-Research-Innovation in South and South-Eastern Asia) is a large-scale Participatory Action Research programme which aims to identify, evidence, and promote effective multi-stakeholder action to tackle the drivers of the worst forms of child labour in selected supply chains in Bangladesh, Nepal, and Myanmar. CLARISSA places a particular focus on participants’ own ‘agency’. In other words, participants’ ability to understand the situation they face, and to develop and take actions in response to them. Most of CLARISSA’s participants are children. This document shares the design and overarching methodology of the CLARISSA programme, which was co-developed with all consortium partners during and since the co-generation phase of the programme (September 2018–June 2020). The immediate audience is the CLARISSA programme implementation teams, plus the Foreign, Commonwealth & Development Office (FCDO). This design document is also a useful reference point for other programmes trying to build large-scale participatory processes. It provides a clear overview of the CLARISSA programmatic approach, the design, and how it is being operationalised in context.

Learning from Life Story Collection and Analysis With Children Who Work in the Worst Forms of Child Labour in Nepal - Karki, Shanta; Apgar, Marina; Snijder, Mieke; Sharma, Ranjana (CLARISSA Learning Note, 2022)
The CLARISSA Nepal team collected and analysed 400 life stories of children and young people engaged in or affected by the worst forms of child labour (WFCL), particularly in the “Adult Entertainment” sector in Nepal, which includes children working in Dohoris (restaurants playing folk music), dance bars, spa-massage parlours, khaja ghars (tea/snack shop) and guest houses. Stories were also collected from children in CLARISSA’s focus neighbourhoods, children in this category include street connected children and those working in transportation, party palaces, domestic labour and construction sites. Of the 400 stories collected, 350 were collected by adult researchers and 50 were collected by children themselves.

Capacity Development in a Participatory Adaptive Programme: the Case of the Clarissa Consortium - Widmer, Mireille; Apgar, Marina; Afroze, Jiniya; Malla, Sudhir; Healey, Jill; Constant, Sendrine (CLARISSA Research and Evidence Paper, 2022)
Doing development differently rests on deliberate efforts to reflect and learn, not just about what programmes are doing and achieving, but about how they are working. This is particularly important for an action research programme like Child Labour: Action- Research-Innovation in South and South-Eastern Asia (CLARISSA), which is implemented by a consortium of organisations from across the research and development spectrum, during a rapidly changing global pandemic. Harnessing the potential of diverse skills and complementary strengths across partners in responding to the complex challenge of the worst forms of child labour, requires capacity to work together in novel ways. This Research and Evidence Paper documents how CLARISSA approached capacity development, and what we learnt from our challenges and successes. From the start, the programme incorporated a capacity development strategy resting on self-assessment of a wide range of behavioural and technical competencies that were deemed important for programme implementation, formal training activities, and periodic review of progress through an after-action review (AAR) process. An inventory of capacity development activities that took place during the first year of implementation reveals a wide range of additional, unplanned activities, enabled by the programme’s flexibility and adaptive management strategy. These are organised into eight modalities, according to the individual or collective nature of the activity, and its sequencing – namely, whether capacity development happens prior to, during, or after (from) implementation. We conclude with some reflections on the emergent nature of capacity development. Planning capacity development in an adaptive programme provides a scaffolding in terms of time, resources, and legitimacy that sustains adaptiveness. We also recognise the gaps that remain to be addressed, particularly on scaling up individual learning to collective capabilities, and widening the focus from implementation teams to individuals working at consortium level.

Evaluating CLARISSA: Innovation Driven by a Participatory Learning Agenda - Apgar, Marina; Snijder, Mieke; Kakri, Shanta; Macleod, Shona; Paul, Sukanta; Sambo, Anna; Ton, Giel (CLARISSA working paper, 2020)
Children end up in child labour as a result of many, often unknown or hidden, interactions between multiple actors and multiple factors within households, communities, and labour systems, leading to unpredictable outcomes for children and other sector stakeholders and sometimes resulting in the worst forms of child labour (WFCL). It is a complex problem, and interventions aimed at tackling it are also, inevitably, complex and challenging. The way they influence change is non-linear, causality is uncertain, and unintended consequences may result. Programmes such as the Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) that are engaging with such intractable challenges and aim to reach the most left behind (children in WFCL) are operating in conditions of complexity. This complexity poses significant challenges to the way programmes are designed, planned, implemented, and evaluated, and requires a move away from linear and predetermined models. In this Working Paper, we share our experience and early learning about how to design and implement monitoring, evaluation and learning that intentionally embraces the challenge of complexity.

Using a ‘Partnership Rubric’ in Participatory Evaluations - Snijder, Mieke; Hicks, Jacky; Paul, Sukanta; Arulanantham, Amit; Apgar, Marina; Afroze, Jiniya; Karki, Shanta; Mareschal, Sophie; Prieto Martin, Pedro; Uddin, Forhad; Veitch, Helen (CLARISSA Learning Note, 2023)
Programmes that aim to tackle complex societal issues, such as the worst forms of child labour, require rich partnerships that bring together different perspectives. CLARISSA’s consortium partnership adopts an empowerment approach to the interventions we deliver and our ways of working together. Part of this approach involves ongoing reflection and learning about how we work together in our partnership, and how this can be adapted if needed. This learning note focuses on a method used in CLARISSA to both reflect on and strengthen how we work in partnerships – the partnership rubric. We found that using the rubric flexibly was key to mitigating some of the challenges of such a complex consortium. This included using it in different sizes of forum, with different levels of preparation. Periodically adapting it for country context and as new partners came on board also helped ensure a shared sense of our preferred ways of working as the project progressed.

Bridging Learning and Action: How Did CLARISSA’s Participatory Adaptive Management Approach Foster Innovation, Effectiveness, and Stakeholder Empowerment? - Prieto Martin, Pedro; Apgar, Marina; Afroze, Jiniya; Arulanantham, Amit; Hicks, Jacqueline; Karki, Shanta; Mareschal, Sophie; Paul, Sukanta; Snijder, Mieke; Uddin, Forhad; Veitch, Helen (CLARISSA Research and Evidence Paper, 2024)
Child Labour: Action-Research-Innovation in South and South-Eastern Asia (CLARISSA) is an evidence and innovation-generation programme funded by the United Kingdom’s Foreign, Commonwealth & Development Office (FCDO), responding to the challenge of the worst forms of child labour (WFCL) in Bangladesh and Nepal. It is a challenge characterised by a poor understanding of its drivers and a lack of evidence on what works to combat it. To handle such fundamental uncertainty, the programme adopts a child-centric and participatory action research approach, which is supported by an adaptive management model to respond better to challenges and opportunities. From its inception, the programme needed to navigate shocks and challenges, such as Covid-19 lockdowns, political upheaval, and sustained budget cuts, which put its capacity to learn and evolve to the test. This paper shares insights emerging from evaluating CLARISSA’s participatory adaptive management (PAM) practices, connecting them with current discussions on adaptive management. It provides an in-depth evaluation of CLARISSA’s PAM approach, exploring how adaptive strategies were implemented and evolved throughout the programme’s life cycle. Multiple cases of adaptation and misadaptation were selected and analysed through a series of in-depth interviews and review of programme documentation, allowing us to assess whether and how the adaptive management practices have been operationalised, the degree to which they led to enhanced decision-making and effectiveness, and their empowering effect on children and other programme stakeholders. Through conceptual analysis and real-world examples, the paper examines the key stages and critical dimensions of PAM, conveying the complexities and dynamism of adaptive management in development work, while highlighting both the successes and challenges encountered in operationalising PAM within CLARISSA.